Bambi - Disney (Bath, Uk : Parragon, 2009)
Share in the adventure of the little fawn Bambi and all his forest friends, as they learn the lessons of life, and discover the power of friendship and love. Experience the magic of Disney by reading and listening along to this classic story of love and friendship again and again.
Location 3A
Keywords: Fiction book